A SMARTBOARD MEDIA IN INCREASING SCIENCE LEARNING INTEREST OF STUDENTS AT SANTA URSULA MIDDLE SCHOOL, JAKARTA - Meita Valentina Zuhro (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Learning is an interaction between teachers, students and the learning environment. The learning environment also includes the learning media facilities owned. This study aims to determine the extent to which the use of smartboard media in increasing the interest in learning science of students at SMP Santa Ursula Jakarta. Data collection techniques used interviews and questionnaires given to 3 science teachers, and 108 students at SMP Santa Ursula Jakarta. The data obtained for the total percentage of student questionnaire results was 80.88% while the total percentage value of the teacher questionnaire results was 87% . Based on the data obtained, it can be concluded that according to participants, the use of smartboards is in the good category in increasing learning interest while according to teachers, the use of smartboards is very good in increasing student learning interest.